2006
DOI: 10.1002/mrc.1935
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR studies of 2‐functionalized 5‐(methylsulfonyl)‐1‐phenyl‐1H‐indoles

Abstract: The 1H and 13C NMR resonances of thirty 2-functionalized 5-(methylsulfonyl)-1-phenyl-1H-indoles were assigned completely and unequivocally using the concerted application of one- and two-dimensional experiments (DEPT, gs-HMQC and gs-HMBC). Finally, the influence of the 2-substituent of 5-(methylsufonyl)-1-phenyl-1H-indoles on the carbon atoms of the indole moiety was estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[13][14][15][16][17][18][19]; and (iv) 5-(methylsulfonyl)-1-phenyl-1H-indole-2-carboxamides (Nos. [20][21][22][23][24][25][26][27][28][29][30], where each containing 14 carbon atoms and consequently a total of 420 chemically non-equivalent carbon centers were obtained from the literature [9]. The chemical structures, numbering and experimental carbon-13 NMR chemical shift values of all 420 atoms in the thirty indole derivatives examined are scheduled in Table 1 and Table S1 …”
Section: Chemical Database Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19]; and (iv) 5-(methylsulfonyl)-1-phenyl-1H-indole-2-carboxamides (Nos. [20][21][22][23][24][25][26][27][28][29][30], where each containing 14 carbon atoms and consequently a total of 420 chemically non-equivalent carbon centers were obtained from the literature [9]. The chemical structures, numbering and experimental carbon-13 NMR chemical shift values of all 420 atoms in the thirty indole derivatives examined are scheduled in Table 1 and Table S1 …”
Section: Chemical Database Setsmentioning
confidence: 99%
“…At the moment, there are approximately 1500 indole alkaloids described [6,7]. In 2003, Cruz-López and coworkers prepared a series of 1-substituted 5-(methylsulfonyl)-1H-indole-2-carboxylic acid esters, -2-nitriles-, and -2-carboxamides by replacing the benzoyl group of indomethacin with a substituted phenyl group [8] and after that, they synthesized some derivatives of this group with different substituents [9]. They found that substitution on the indole nitrogen atom with the pmethylthiophenyl group on N-butyl and N-pentyl-2-carboxamides provided active and selective COX-2 enzyme inhibitors.…”
Section: Introductionmentioning
confidence: 99%